Revisiting Density Concepts for City Planning and Its Implications for Dhaka City - Khan, Adil Mohammed; Hossain, S M Nawshad; Reza, Farhadur (Journal of Bangladesh Institute of Planners, 2017)
Density of urban areas plays a crucial role in planning and managing the urban development both at the city and neighborhood levels, which subsequently affects the livability. Density describes the number of people in a given area and is usually expressed as the number of people per acre or dwelling units per acre. This paper explores various concepts of density and its application in urban planning across various cities in the world and recommends for density implications in city planning for Dhaka city as well. There are huge variations in density in various cities around the world and therefore both the form and style of urban development varies drastically across the globe. Density zoning has been incorporated in the Detailed Area Plan (DAP), 2016-2035 for Dhaka city aiming to reduce pressure of population as well as ensure balanced development to make the city livable and sustainable. In addition to density considerations, carrying capacity of an urban area is an important indicator for measuring livability and sustainability of development of an area. This paper reveals that most of the wards of Dhaka city have exceeded its carrying capacity to a great extent impacting livability of the city and suggesting for density planning for the city to increase the livability and functionality of the city. This study recommends for mid-rise residential developments for Dhaka city, which is desirable for residential living that creates better communities, neighborhoods and societies. JBIP, Vol. 10, 2017 (Printed in December 2019), pp. 01-13